A survey of Malaysian consultants on construction claim problems / Nor Azmi Bakhary, Hamimah Adnan and Azmi Ibrahim - Bakhary, Nor Azmi; Adnan, Hamimah; Ibrahim, Azmi (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
The construction industry in Malaysia is very complex as it involves multidisciplinary participants. In this environment, claims appear to cause delays and hold back the completion of a construction project. Construction contracts are rarely perfect, and claims for time extensions and additional costs often have to be made by one party on another. The extensively increasing number of construction claims indicates the need for the implementation of an effective construction claim management. This research is aimed at surveying the most common problems experienced by Malaysian contractors in construction projects. This paper presents the survey results and main findings from the consultants' points of view which indicate that inaccessibility or unavailability of relevant documents, the lack of site staff awareness to proactively detect claims and understanding the contract itself and conflicts arising during owner/contractor negotiation are all critical problems associated with the process of claim management. The problems observed from this research could be used to improve the contractors' claim management system.